Novel composite siro-spinning with forced migrations of filaments. Issue 19 (October 2019) - Xia, Zhigang; Wang, Cancan; Fu, Chiyu; Wei, Jiang; Xu, Weilin
In this study, a novel composite siro-spinning method with cyclically migrating filaments was developed as a simple and safe way to enhance filament-staple-fiber coherence. The novel composite siro-spinning method was theoretically demonstrated to produce a yarn with migrated filaments clasping both internal and external fibers. It was predicted that migrated filaments of the novel composite sirospun yarn were not straight enough to resist yarn tensile drawing as the filament parallelism with the yarn axis decreased. However, migrated filaments could clasp the staple fibers firmly to enhance filament-staple-fiber coherence, contributing an excellent frictional resistance of the novel composite yarn. Experiments were then conducted to validate the demonstration. Experimental results proved that the novel composite sirospun yarn had cyclic filament immersion and exposure appearance, resulting in medium hairiness and yarn imperfection after comparison with corefil sirospun and siro corefil yarns. The novel composite sirospun yarn with severe filament migrations had poor filament straightness, but filament deformations that were effective in clamping staple fibers. Therefore, the novel composite sirospun yarn had less strength, but greater frictional resistance than corefil sirospun and siro corefil yarns.